The Moderating Role of Celebrity Endorsers in The Relationship Between Social Media Marketing Effort and Intention to Purchase Which Is Mediated by Brand Awareness at PT Sugarlab Royal Beauty - Diana Syarifah; Teofilus Teofilus; Romauli Nainggolan (Eduvest - Journal of Universal Studies, 2025)
In the digital era, social media has become a powerful platform for brand promotion, with celebrity endorsers playing a key role in influencing consumer behavior. This study aims to evaluate celebrity endorsers' impact on enhancing Miracle Face Mist Sugarlab's brand awareness and examine the relationship between social media marketing efforts, brand awareness, and purchase intention. A quantitative approach was employed, and data were analyzed using Multiple Regression Analysis (MRA) through the SPSS Process tool to test the proposed hypotheses. The study focused on identifying how digital celebrity endorsements affect brand perception and consumer decision-making. The findings indicate that both social media marketing activities and the presence of celebrity endorsers significantly increase brand awareness. Furthermore, brand awareness was found to affect consumers’ intention to purchase the product strongly. These results highlight the importance of strategic influencer collaboration and effective social media engagement in driving brand visibility and consumer interest. The implications of this research suggest that beauty and skincare brands can optimize marketing outcomes by leveraging well-targeted celebrity endorsers in digital campaigns, thereby enhancing consumer trust and purchase likelihood.